Defect accumulation in swift heavy ion-irradiated CeO2 and ThO2. Issue 24 (30th May 2017) - Palomares, Raul I.; Shamblin, Jacob; Tracy, Cameron L.; Neuefeind, Joerg; Ewing, Rodney C.; Trautmann, Christina; Lang, Maik
Abstract : Neutron total scattering is applied to investigate effects of ion irradiation, which is a promising means for improving oxygen conductivity. Abstract : Neutron total scattering was used to investigate defect accumulation mechanisms in CeO2 and ThO2 irradiated with 2.2 GeV Au ions. Pair distribution function (PDF) analysis was applied to characterize the local structural evolution and irradiation-induced defects as a function of irradiation fluence. CeO2 exhibits a greater amount of disorder than ThO2 under the same irradiation conditions. The local structures of the two materials evolve differently as a function of ion fluence, even if similar defects are produced. The PDF analysis indicates that oxygen dimer and/or peroxide defects with 〈O–O〉 distances of ∼1.45 Å are formed in CeO2, while irradiation-induced defects in ThO2 result in a change in the mean O–Th–O bond angle and a distortion of local ThO8 polyhedra. Understanding how bound oxygen defects, such as peroxide, affect bulk oxygen transport in CeO2 will aid in better predicting and improving properties of fluorite structure materials for fast ion conductor applications.